Métodos de utilizar el forraje - Alba, Jorge de (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Soiling as a system of harvesting forage, eliminates the possibility of selection of the forage intake that is inherent in grazing. But overgrazing also results in poor chances for selection. As overgrazing increases the differences between soiling and grazing are reduced. Rotational grazing results in greater numbers of stock possible per hectare, but not necessarily higher production per cow unless very low rates of stocking are used. The longer the rotation the greater the total yield, but this increase in yield results in lowering of quality of the forage. Therefore systems of grazing which allow the use of more mature grass are likely to result in less production per individual, but this loss can be compensated by the use of more animals per unit area. No one system is really superior to another unless all these principles are taken into consideration and what seems to be the best method for one set of circumstances may be completely inadequate under different circumstances.